DEVELOPING A MODEL OF TEACHING READING COMPREHENSION FOR EFL STUDENTS - Hamra, Arifuddin; Syatriana, Eny (TEFLIN Journal, 2015)
This study aimed at designing a model of teaching reading comprehension based on the objectives of teaching reading at the senior high school and the teachers’ understanding of the school curriculum and to describe the implementation of the model. The subject consisted of 24 teachers, 167 students of five SMAs (senior high schools) in South Sulawesi, Indonesia. This developmental study had five steps: analysis, design, development, implementation, and evaluation. The result indicates that the model significantly increases the reading comprehension of EFL students (M= -14.43114), t(166) = -16.155, p <.05. The teachers and students stated that the learning condition, teaching and learning process, reading comprehension, instructional reading materials, and teachers’ teaching performance were well established. This interactive model improved the reading comprehension of the students significantly. Thus, it is an alternative model of teaching reading for EFL students.